Coronil effectively inhibits the interaction of clinically relevant Omicron mutants of SARS-CoV-2 spike proteins with human ACE2 receptor - Acharya Balkrishna; Rishabh Dev; Sandeep Kumar; Anurag Varshney (Phytomedicine Plus, 2025)
Background: Accumulating evidence suggests that the receptor binding domain (RBD) of the SARS-CoV-2 Omicron variant has several times more binding affinity to the human angiotensin-converting enzyme 2 (ACE2) receptor compared to the RBD of the original Covid-19 strain. This increased binding affinity of the Omicron variant is responsible for its increased internalization and infectivity. Purpose: In the present study, the impact of Coronil, a tri-herbal formulation of extracts from Withania somnifera, Tinospora cordifolia and Ocimum sanctum on the binding properties of Omicron SARS-CoV-2 variant spike proteins (S proteins) was investigated. Methods: Chemical composition of Coronil was determined by the Prominence-XR UHPLC system. The ELISA-based ACE2 binding inhibition assay was performed to delineate the effect of Coronil on the interaction between human ACE2 receptor and different Omicron variant S-proteins such as BA.4/BA5, XBB, BA.2.75.2, BA4.6/BF.7, BA.2.75.2, BQ.1.1 and a recently found spike protein variant JN.1 which is thought to emerge from BA.2.86. Results: Coronil showed a dose-dependent inhibitory effect on the interactions between ACE2 and receptor binding domains (RBD) of all variants of S-proteins evaluated in this study including the recently emerged, highly transmissible variant spike protein JN.1. Although, Coronil significantly reduced the binding percentage in almost all the variant spike proteins, the maximum inhibition was achieved against BA.4/BA.5 where it inhibited the S protein – ACE2 interaction even at a low concentration of 3 µg/ml (16.6 %). This binding inhibition was further increased to 60.3 and 84.3 % at 100 and 300 µg/ml respectively. Conclusion: This capability of Coronil to inhibit the binding of S-protein variants with ACE2 receptor may interfere with viral binding and internalization resulting in reduced infectivity of these Omicron spike protein variants. Overall, our data underscores the potential of Coronil in combating the various newly emerged Omicron spike protein variants. These findings may provide a basis for further studies of Coronil for its clinical effectiveness against these Omicron variants.